An Analysis on Students’ Writing Problems in Academic Writing Class of English Department STKIP PGRI Tulungagung in Academic Year 2017/2018 - Palupi, Retno; Septiana, Ayu Rizki (Pendidikan Bahasa Inggris (Universitas Internasional Batam), 2018)
English has an important role in international daily life as tool communication.  As the foreign language, students do not usually use English in their daily activities. So it makes the students have problems faced in each skill. In university especially English Department, Academic Writing course is required to be taken by students. In this research, the researcher wants to analyse the problems and the sources in the Academic Writing class. The research method used is qualitative research method. The samples are 23 students in the fourth semester. The research instruments used in this research are test and interview. Based on the research findings of 23 students who submitted the Argumentative text, there were 95 mistakes. The most mistakes in grammatical problems there were 23 mistakes (24.21%), and in problems of sentence structure there were 21 mistakes (22.10%). From 23 students who interviewed by the researcher, the most sources of the problem when they wrote an essay were; 20 students have problems on the nature of the writing process, and 21 students have problem because of inadequate time.